O exercício físico reduz parâmetros comportamentais e moleculares envolvidos na drogadição por anfetamina em ratos: envolvimento da via opioide endógena - Rosa, Higor Zuquetto (2023)
The mesolimbic dopaminergic system constitutes a drug target circuit, whose neuroplasticity alteration is involved in the development of drug addiction. Due to this neuromodulation, currently available treatments only relieve the initial symptoms of drug withdrawal, not reaching the molecular basis of the disease. Based on this, our group has investigated the beneficial influence of physical exercise (PE) on drug addiction, by activating the release of endogenous opioids (EO). Furthermore, it is pointed out that psychostimulant drugs are also capable of favoring the release of EO, thus arousing interest in the study of this mechanism. Therefore, it is necessary to elucidate the relationship between the practice of PE and the administration of psychostimulants, such as amphetamine (AMPH), considering the activation of the EO system, in search of support for new treatments for drug addiction. Thus, the studies that make up the present thesis were developed through 3 experimental protocols: I) exposure of rats to the conditioned place preference protocol (CPP) with AMPH, the practice of PE during drug abstinence and concomitant administration of naloxone (NAL), to inhibit the activation of the EO system induced by PE, evaluation of drug relapse, as well as of dopaminergic molecular markers, in the mesolimbic region (Ventral Tegmental Area (VTA) and Nucleus accumbens (NAc)); II) exposure of rats to AMPH, to the PE protocol with the EO system inhibited by the administration of NAL, reexposed to AMPH and evaluation of neurotrophic molecular markers in VTA and NAc; III) the blockade of the EO system, with administration of NAL, was performed before conditioning with AMPH in the CPP, in which the preference for the drug and the levels of monoamines in the VTA and NAc were evaluated. In addition to the behavioral assessments of preference and relapse by AMPH, locomotor, and memory performance were also quantified, to monitor any artifact that could falsify the hedonic response to the drug. Taken together, the studies that make up this thesis showed that the activation of the EO system induced by PE was able to prevent AMPH relapse behaviors and increase the immunoreactivity of dopaminergic molecular markers and neurotrophins in VTA, reducing them in the NAc. In addition, conditioning with AMPH also allowed us to confirm the activation of the OE system, which we interpreted as a modulatory response of the organism in search of a balance of the psychostimulant activity induced by the drug. This response was evidenced through the quantification of monoamines in the mesolimbic system, whose metabolite levels showed agreement with the hedonic effects observed in the CPP. In this context, it is possible to deduce that the reduction in drug-seeking relapse behavior induced by PE was consequent to the modulation of the EO system in the mesolimbic area, thus disfavoring drug addiction. Considering that drug addiction is a serious public health problem, whose pharmacological treatments do not have the desired efficacy, unraveling neural mechanisms and their adjacent molecular bases will contribute to the achievement of future therapeutic approaches for drug addiction.